Political, economic and social influences on Moon Jae-In's policy changes in THAAD deployment - Rostineu Rostineu; Syahroni Reza Ali (Journal of Korean Applied Linguistics, 2021)
This research discusses the attitude of President Moon Jae-In in THAAD placement. THAAD is a defense system against short and medium-range missiles. In February 2016, South Korea and the United States reached an agreement on the plan to deploy Terminal High Altitude Area Defense or THAAD in South Korea. In the process of reaching this agreement, South Korea faces complex considerations that are both internal (increasing national security) and external (possible resistance from China and Russia). Moreover, in the middle of the process of implementing THAAD placement, there was a change of government from Park Geun-Hee to Moon Jae-In. China used several official and unofficial media to pressure South Korea during Park Geun-Hee's reign. This problem continued until the government changed to Moon Jae-In, but in the end the THAAD problem was resolved. This background leads to the research question: what factors are contributing behind Moon Jae-In's attitude regarding THAAD placement? By applying the descriptive-analysis method with data sources in the form of online media, this study aimed to explain the background that drove Moon Jae-In to resolve conflicts related to THAAD placement. The results of the analysis showed that there were political, economic, and social factors that drived changes related to the conflict over the placement of THAAD during the reign of Moon Jae-In.